2015
DOI: 10.1039/c4fo00610k
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and chemical identification of lipid derivatives from avocado (Persea americana) pulp with antiplatelet and antithrombotic activities

Abstract: Platelets play a pivotal role in physiological hemostasis. However, in coronary arteries damaged by atherosclerosis, enhanced platelet aggregation, with subsequent thrombus formation, is a precipitating factor in acute ischemic events. Avocado pulp (Persea americana) is a good source of bioactive compounds, and its inclusion in the diet as a source of fatty acid has been related to reduced platelet aggregability. Nevertheless, constituents of avocado pulp with antiplatelet activity remain unknown. The present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 48 publications
0
36
0
Order By: Relevance
“…In fact, the lipophilic extract of the fruit had higher antioxidant capacity than its hydrophilic extract [83]. A study indicated that avocado pulp, containing acetogenin compounds, inhibited platelet aggregation with a potential preventive effect on thrombus formation [84]. Moreover, avocado pulp contains variable oil contents and is widely used in many fields such as the pharmaceutical industry [82].…”
Section: Experimental Studiesmentioning
confidence: 99%
“…In fact, the lipophilic extract of the fruit had higher antioxidant capacity than its hydrophilic extract [83]. A study indicated that avocado pulp, containing acetogenin compounds, inhibited platelet aggregation with a potential preventive effect on thrombus formation [84]. Moreover, avocado pulp contains variable oil contents and is widely used in many fields such as the pharmaceutical industry [82].…”
Section: Experimental Studiesmentioning
confidence: 99%
“…The main reason for the increase in planted area with avocado is based on the growth of the international demand. This phenomenon is a consequence of the multiple health benefits consumers perceive in this fruit, in addition to its pleasant flavor (Pérez-Méndez & García-Hernández, 2007;Rodriguez-Sanchez et al 2015;Monika & Geetha, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Our research group has purified and studied acetogenins, naturally occurring lipidic molecules from avocado fruit, which show a wide range of bioactivities including antimicrobial, antioxidant, antiplatelet, and antithrombotic (Hernández‐Brenes and others ; Rodríguez‐Sánchez and others, , , ). Two new structures were reported (Rodríguez‐Sánchez and others ) and, recently, two putative acetogenins were identified in a study with 22 avocado cultivars (Rodríguez‐López and others ), extending the acetogenin pool to eight molecules.…”
Section: Introductionmentioning
confidence: 99%